2022
DOI: 10.1139/cjss-2022-0026
|View full text |Cite
|
Sign up to set email alerts
|

Perennial grain Kernza® fields have higher particulate organic carbon at depth than annual grain fields

Abstract: Conversion from annual to perennial grains such as intermediate wheatgrass Kernza® could sequester soil organic carbon (SOC). To date, no studies have quantified SOC under Kernza on working farms. We sampled three sites with paired fields under annual grains and converted to Kernza 5–17 years ago to 100 cm and compared their SOC stocks as distributed between mineral-associated organic matter (MAOM) and particulate organic matter (POM). POM-C was higher under Kernza cultivation but total and MAOM-C were similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…An important exception is perennial rice, which produces similar yields to annual rice and provides greater economic returns (Zhang et al., 2022a). Perennial grains often lead to greater labile soil organic C concentrations than annual grain systems (Culman et al., 2013; Sprunger et al., 2019; van der Pol et al., 2022) though changes can be inconsistent over time and location (Kim et al., 2022). Eddy covariance observations indicate that perennial Kernza provides a stronger C sink than annual crops (de Oliveira et al., 2018), however; significant gains in total soil organic C stocks due to perennial grain cropping have been infrequently detected (Zhang et al., 2022a).…”
Section: Approaches To Increase Soil C Storage Through Plant Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…An important exception is perennial rice, which produces similar yields to annual rice and provides greater economic returns (Zhang et al., 2022a). Perennial grains often lead to greater labile soil organic C concentrations than annual grain systems (Culman et al., 2013; Sprunger et al., 2019; van der Pol et al., 2022) though changes can be inconsistent over time and location (Kim et al., 2022). Eddy covariance observations indicate that perennial Kernza provides a stronger C sink than annual crops (de Oliveira et al., 2018), however; significant gains in total soil organic C stocks due to perennial grain cropping have been infrequently detected (Zhang et al., 2022a).…”
Section: Approaches To Increase Soil C Storage Through Plant Breedingmentioning
confidence: 99%
“…Perennial grains often lead to greater labile soil organic C concentrations than annual grain systems (Culman et al, 2013; Crop Science F I G U R E 6 Diagram illustrating hypothesized breeding targets for soil carbon storage, agricultural intensification, and both. Sprunger et al, 2019;van der Pol et al, 2022) though changes can be inconsistent over time and location (Kim et al, 2022). Eddy covariance observations indicate that perennial Kernza provides a stronger C sink than annual crops (de Oliveira et al, 2018), however; significant gains in total soil organic C stocks due to perennial grain cropping have been infrequently detected (Zhang et al, 2022a).…”
Section: Year Of Releasementioning
confidence: 99%
“…Pastures and forage crops are well known for their ecosystem service benefits (e.g., soil health), and have large ranges that encompass many different cropping systems (Aponte et al, 2019;Martin et al, 2020;Teixeira et al, 2021). The perennial grain Kernza is one example of the potential for perennial crops to improve soil quality and water regulation (Audu et al, 2022;Rakkar et al, 2023;Reilly et al, 2022;van der Pol et al, 2022) perennials to provide these ecosystem benefits is one reason they are a powerful climate adaptation tool. Perennials also have a longer growing season than annuals, thus allowing these crops to capture and utilize water that is available outside the typical annual crop growing season (Vico & Brunsell, 2018).…”
Section: 3mentioning
confidence: 99%
“…Perennial crops generally have a longer photosynthetic season, which increases yearly light interception and enhances productivity 15 . In addition to permanent living cover, deep roots of perennial crops have been shown to increase nitrogen (N) retention 11,12 and soil carbon accumulation 16,17 and may ultimately require lower rates of fertilizer, pesticide and labour inputs 9 . Perennial cropping systems can also be managed to produce both grains and forages in mixed crop-livestock systems 5,[18][19][20][21] .…”
Section: Performance and Adoptionmentioning
confidence: 99%
“…These data collectively showed that the PR lines we developed had agronomic traits resembling domesticated AR yet retained from the perennial O. longistaminata parent the ability to regrow vigorously after harvest. From next-generation sequencing, 16.16% of the PR23 genome was O. longistaminata.…”
mentioning
confidence: 99%